Ozone Exposure of a Weed Community Produces Adaptive Changes in Seed Populations of Spergula arvensis - Landesmann, Jennifer Brenda (2013)
Tropospheric ozone is one of the major drivers of global change. This stress factor alters plant growth and development. Ozone could act as a selection pressure on species communities composition, but also on population genetic background, thus affecting life history traits. Our objective was to evaluate the consequences of prolonged ozone exposure of a weed community on phenotypic traits of Spergula arvensis linked to persistence. Specifically, we predicted that the selection pressure exerted by high ozone concentrations as well as the concomitant changes in the weed community would drive population adaptive changes which will be reflected on seed germination, dormancy and longevity. In order to test seed viability and dormancy level, we conducted germination experiments for which we used seeds produced by S. arvensis plants grown within a weed community exposed to three ozone treatments during four years (0, 90 and 120 ppb). We also performed a soil seed bank experiment to test seed longevity with seeds coming from both the four-year ozone exposure experiment and from a short-term treatment conducted at ambient and added ozone concentrations. We found that prolonged ozone exposure produced changes in seed germination, dormancy and longevity, resulting in three S. arvensis populations. Seeds from the 90 ppb ozone selection treatment had the highest level of germination when stored at 75% RH and 25 °C and then scarified. These seeds showed the lowest dormancy level when being subjected to 5 ºC/5% RH and 25 ºC/75% followed by 5% RH storage conditions. Furthermore, ozone exposure increased seed persistence in the soil through a maternal effect. Given that tropospheric ozone is an important pollutant in rural areas, changes in seed traits due to ozone exposure could increase weed persistence in fields, thus affecting weed-crop interactions, which could ultimately reduce crop production.